COMPLICATIONS IN THE POSTOPERATIVE PERIOD IN PATIENTS WITH COMBINED TRAUMATIC BRAIN INJURY - Aliev Mansur Abdukholikovich (Research Focus International Scientific Journal, 2025)
This study analyzes postoperative complications, mortality factors, and outcomes in 127 patients with severe combined traumatic brain injury (TBI) treated between 2020 and 2024. The research demonstrated that postoperative morbidity was largely determined by the severity of injury, patient age, preoperative neurological status, timing of surgery, and intraoperative management of cerebral edema. The overall postoperative mortality rate was 7.9%. Major predictors of death included brainstem lesions, massive brain edema with herniation, secondary hemorrhages, and delayed surgical intervention. Age-related comorbidities, such as hypertension, atherosclerosis, and pulmonary complications, contributed significantly to unfavorable outcomes in elderly patients. The study emphasizes that early surgical decompression, adequate anti-edema therapy, and comprehensive neurocritical care are essential for improving survival and functional recovery in patients with severe TBI.